PENGARUH KEMAMPUAN KOGNITIF TERHADAP KETERAMPILAN PENERIMAAN SERVIS PADA EKSTRAKURIKULER TENIS MEJA DI SMA NEGERI 89 JAKARTA - Ramadhan, Rizky; Siswanto; Zinat Achmad, Irfan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of cognitive ability on service reception skills in table tennis extracurricular activities at SMA Negeri 89 Jakarta. The research used a quantitative approach with a causal associative method and ex post facto design. The population consisted of 20 students participating in the table tennis extracurricular activity for the 2025/2026 academic year, with a total sampling technique. Data were collected through a cognitive ability test using a Guttman scale (true/false format) covering cognitive dimensions C1 to C6 (19 valid items), and a service reception skill test with 30 trials assessed using a structured observation rubric. Data analysis was performed using simple linear regression through SPSS version 31. Descriptive statistics showed a mean cognitive ability score of 67.80 and a mean service reception skill score of 78.70. Normality test using Shapiro-Wilk indicated that both variables were normally distributed (sig. > 0.05). Linearity test showed a significant linear relationship (sig. deviation from linearity = 0.716). However, the results of simple linear regression showed F = 0.200 with sig. = 0.660 (> 0.05) and R² = 0.011, indicating that cognitive ability did not have a significant effect on service reception skills and only contributed 1.1% to it. These findings suggest that at the beginner-to-intermediate stage, technical factors and practice frequency are more dominant than cognitive ability measured through written tests.